2008
DOI: 10.1016/j.rmed.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms among residents of a heavy-industry province in China: Prevalence and risk factors

Abstract: The crude PRs of symptoms were lower than those reported by European and American studies but closer to those of previous Chinese studies. The risks of respiratory symptoms in this population were increased by smoking, occupational exposures to dust and gas, and combined residence-related exposures such as living close to a main road, factory or chimney, indoor coal use and the presence of irritating smoke during cooking, among other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
4
22
0
3
Order By: Relevance
“…Previous studies reported risk differences for health effects associated to PM concentration [20,21]. With respect to PM concentration and the observed high prevalence of respiratory outcomes, the study results are consistent with those conducted elsewhere [20,21,22]. This study did not find any association between poor respiratory health and gender, which could be due to the small sample size which may not have been sufficient to detect gender differences.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies reported risk differences for health effects associated to PM concentration [20,21]. With respect to PM concentration and the observed high prevalence of respiratory outcomes, the study results are consistent with those conducted elsewhere [20,21,22]. This study did not find any association between poor respiratory health and gender, which could be due to the small sample size which may not have been sufficient to detect gender differences.…”
Section: Discussionsupporting
confidence: 89%
“…Exposure to smoking (OR, 2.06e5.02), occupational dust (OR, 1.35e1.72), occupational gas (OR, 1.48e1.72), and presence of irritating smoke during cooking (OR, 1.54e2. 22) were closely related to persistent cough, persistent phlegm and wheeze, as well as to asthma. 22 Coal and biomass fuels Stoves fueled by coal or biomass, which are major sources of indoor combustion, release respiratory irritants such as particulate matter (PM), carbon monoxide (CO), sulfur dioxide, NO 2 , and organic toxins.…”
Section: Chemical Contaminantsmentioning
confidence: 96%
“…22) were closely related to persistent cough, persistent phlegm and wheeze, as well as to asthma. 22 Coal and biomass fuels Stoves fueled by coal or biomass, which are major sources of indoor combustion, release respiratory irritants such as particulate matter (PM), carbon monoxide (CO), sulfur dioxide, NO 2 , and organic toxins. Burning biomass fuels, mainly wood, crop residues, and livestock dung, remain as the important source of exposure to a variety of toxins.…”
Section: Chemical Contaminantsmentioning
confidence: 96%
“…Another study that involved 31,704 adults from 6 cities in Liaoning, China, failed to find an association between asthma prevalence and ambient TSP, SO 2 , and NO 2 exposures. 24 However, certain residential exposures to air pollutants appeared to be associated with the prevalence of asthma, although such a relationship was only assessed by questionnaire and not objective ). Another study from China using questionnaire surveys rather than actual pollutant measurement found cooking coal smoke was associated with physician-diagnosed adult asthma (OR, 2.53; 95% CI, 1.02-6.61).…”
Section: Air Pollutant Exposures On Allergy Prevalence In Asian Adultsmentioning
confidence: 99%